Penentuan Lokasi Menggunakan Metode Analytic Hiearachy Process Pada PT XYZ - Nova Pangastuti (LPPM Universitas Bina Sarana Informatika, 2022)
The company PT.XYZ is one of the manufacturing companies engaged in the manufacture of bicycles with small and large sizes. This company is experiencing problems with the increasing demand for bicycle orders. The constraints experienced by the company are the selection of locations to build new locations due to the increasing number of requests, after that the next thing that becomes important for a company is knowing the supply line from the company to several distributors, selecting alternative vehicles, production planning to overcome the increase in orders by the company. customer. In addition, the company needs to introduce a way of selling bicycles based on the internet in the form of a web because people already know how using bicycles is good for the environment. The data taken were selected from three locations called Location A, Location B, and Location C. The three locations have different characteristics and many problem so it is necessary to calculate using the Analytic Hierarchy Process Method. The location selection was chosen based on the calculation of the WSV Value, Index Consistency and Ratio.